Percutaneous Nephrolithotomy Complications in 671Consecutive Patients: A Single-Center Experience - Mousavi-Bahar, Seyed Habibollah; Mehrabi, Sasan; Moslemi, Mohammad Kazem (Urology Journal, 2011)
Purpose: To evaluate major and minor complications of percutaneous nephrolithotomy (PCNL) and their management in our consecutive cases. Materials and Methods: We reviewed medical records of 671 patients who had undergone PCNL in our center from March 2000 to March 2006. The demographic data, stone parameters, PCNL complications, and stone-free rate were evaluated. Multiple parameters were evaluated for their association with PCNL complications using Chi-Square test. Results: Complications occurred in 203 (30.3%) patients; renal parenchymal injury in 103 (15.4%), peri-operative bleeding in 42 (6.3%), late bleeding in 6 (0.9%), renal collecting ducts injury in 35 (5.2%), fever in 7 (1.0%), colon perforation in 2 (0.3%), major vessels injury in 3 (0.4%), pneumothorax in 3 (0.4%), and hemothorax in 2 (0.3%) subjects. Mortality occurred in 1 patient with colon perforation (0.15%). Conclusion: Percutaneous nephrolithotomy has low complication rate in experienced hands.